PERLINDUNGAN HUKUM TERHADAP WARTAWAN DALAM MELIPUT AKSI DEMONSTRASI DI KOTA SAMARINDA MENURUT UNDANG-UNDANG NOMOR 40 TAHUN 1999 TENTANG PERS - Aris Tianlee (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSRACT Press both print and electronic instrument in order to live a very vital community for improving the quality of life of its citizens. in addition to its function as a medium of information and communication, the press is also a reflection of identity the community because what is in the press reminds us of the presence in the pour is the pulse of public life where the press are. Legally formal indeed journalists obtain a guarantee of legal protection in the exercise of his duties, but in practice in the field of violence against journalists and other media crew either in the form of threats/intimidation and pressure from the parties become the object of news as well as acts of beating, seizure or destruction of journalistic duty gear until the killing of people press. Goals and purpose of writing To know us form of legal protection of journalists in covering the action demonstration in the town of Samarinda. To know the efforts of antisemitic laws against journalists who are experiencing violence in covering the action demonstration in the town of samarinda. The author uses the method of empirical juridical approach. Background the occurrence of acts of violence on journalists while covering a demonstration of action is due to the (2) two factors, namely the internal factors and external factors. The internal factor is the occurrence of acts of violence on the reporter's own negligence or fault of the less heart a heart or less meticulous when covering the demonstration, while action eksternalnya factor is the occurrence of acts of violence on the journalist because of the element of deliberate action of a Party feel aggrieved or feel dissatisfied will fill made news as well as other forms of violence experienced by reporters covering the action demonstration in the city of Samarinda is very diverse, ranging from the form stoning, persecution, deprivation of the tool, then, intimidation, threats to murder. Keywords: Legal Protection Of Journalists